(untitled) (Scientific journal of the Fergana State University, 2023)
In the education system, it is necessary to ensure the interconnection, compatibility and prospects of the components of the pedagogical system for the education of a mature, creative personality in all respects, for the continuous development of the student at all stages of the educational process. Socio-pedagogical problems of the development of creativity of students of technical creativity and construction sciences, organizational bases for the activity of technical creativity, invention, discovery, rationalization proposals and patent information, methods for solving creative problems, modeling and design, management of students’ technical creativity, technical creativity in various institutions are covered topics related to the organization of activities, methods of development of creativity and it is planned to provide them with knowledge. Providing students with technological education includes general patterns studied in the sciences of the natural science cycle, about the main branches of current production, the device and principles of operation of the latest machines, mechanisms and tools, as well as their practical application use, basic materials and their use, is to provide general information about new technological processes, scientific knowledge and general information about the organization of work on a scientific basis. These tasks are successfully implemented in the process of technical design and modeling of modern technology.